Case Report: A de novo Variant in NALCN Associated With CLIFAHDD Syndrome in a Chinese Infant - Liao, Zhenyu; Liu, Yali; Wang, Yimin; Lu, Qin; Peng, Yu; Liu, Qingsong (Frontiers in Pediatrics, 2022)
Background: NALCN encodes a sodium ion leak channel that regulates nerve-resting conductance and excitability. NALCN mutations are associated with two neurodevelopmental disorders, one is CLIFAHDD (autosomal dominant congenital contractures of the limbs and face, hypotonia, and developmental delay, OMIM #616266) and another is IHPRF (infantile hypotonia with psychomotor retardation, characteristic facies 1, OMIM #615419). Case presentation: In the current study, a Chinese infant that manifested abnormal facial features, adducted thumbs, and neurodevelopmental retardation was diagnosed with CLIFAHDD syndrome. Trios-based Whole-exome sequencing revealed that the infant harbored a de novo variant of the NALCN gene (c.4300A>G, p.I1434V). Conclusions: Our findings further enriched the variant spectrum of the NALCN gene and may expand the clinical range of NALCN-related disorders.